1988
DOI: 10.1093/brain/111.6.1299
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Vestibulo-Ocular Reflex, Smooth Pursuit and Eye-Head Tracking Dysfunction in Internuclear Ophthalmoplegia

Abstract: Vertical smooth eye movements were quantified by magnetic search coil oculography in 7 patients with internuclear ophthalmoplegia (INO), 4 bilateral and 3 unilateral, and compared with age-matched normal subjects. The upward and downward vestibulo-ocular reflex (VOR) had reduced gain and abnormal phase lag in both unilateral and bilateral INO during active head motion at frequencies from 0.25 to 2 Hz. The phase lag was attributed to disruption of vestibular eye velocity signals and relative preservation of eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 0 publications
1
30
0
Order By: Relevance
“…The lesion in our patient was extended to just ventral of the fourth ventricle dorsally and spread through the whole pons vertically. Both bilateral MLF [8,9] and the PMT cell groups [4] can be considered as possible structures of impaired vertical gaze holding in the pontine level. Because our patient had a unilateral INO, however, lesion in PMT cell groups might be the more possible cause of the vertical GEN.…”
Section: Discussionmentioning
confidence: 99%
“…The lesion in our patient was extended to just ventral of the fourth ventricle dorsally and spread through the whole pons vertically. Both bilateral MLF [8,9] and the PMT cell groups [4] can be considered as possible structures of impaired vertical gaze holding in the pontine level. Because our patient had a unilateral INO, however, lesion in PMT cell groups might be the more possible cause of the vertical GEN.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the MLF is probably and the BC possibly also involved in the transmission of upward excitatory vestibular signals [1,2,14] . However, whatever the actual role of the BC, it would appear that upward vestibular signal transmission depends on both the MLF and the CVTT, whereas downward vestibular signal transmission appears to depend only upon the MLF [2] .…”
Section: Other Pathways Involved In Upward Vestibular Eye Movementsmentioning
confidence: 99%
“…Although many studies have confirmed the validity of these tests by making precise measurements of eye movements ( Fig. 1) [6,7,15,24,28], they remain clinical methods that are easy to elicit and interpret, provided the examiner understands what to look for.…”
Section: Introductionmentioning
confidence: 99%